Proteins from microalgae for the stabilization of fluid interfaces, emulsions, and foams. (February 2021) - Bertsch, Pascal; Böcker, Lukas; Mathys, Alexander; Fischer, Peter
Abstract: Background: Microalgae and cyanobacteria are expected to play a key role as sustainable protein source in future food production systems. Besides nutritional aspects, microalgae proteins are increasingly screened for their technofunctional potential, including the stabilization of emulsions and foams. Emulsions and foams are ubiquitous in the food, cosmetic, and pharmaceutical industry and are generally stabilized by synthetic surfactants or proteins of animal origin. Here, we assess the potential of microalgae proteins as green alternative to stabilize fluid interfaces. Scope and approach: The use of microalgae proteins for stabilization of fluid interfaces is reviewed from fundamental adsorption kinetics and interfacial elasticity to the formation and stability of emulsions and foams. Special emphasis is paid to microalgae extract purification regarding functionality and resource efficiency. The microalgae proteins are critically compared to currently employed proteins with respect to interfacial performance, economic, and environmental aspects. Key findings and conclusions: Microalgae proteins exhibit comparable to superior interfacial stabilization compared to animal or plant based proteins. Their emulsions and foams exhibit minor pH-dependency due to a characteristically low isoelectric point and extraordinary resistance towards increased ionic strength. Minimally processed disruptured cells allow the stabilization of basic emulsions. Fractionation into a soluble extract or protein isolation considerably enhance protein functionality, but are associated with higher production efforts and lower protein yields. We conclude that microalgae proteins have the potential to replace surfactants and animal based proteins for the stabilization of emulsions and foams, and protein extraction for interfacial stabilization could provide added value for future microalgae biorefinery concepts. Highlights: Fundamentals: Adsorption kinetics and interfacial elasticity at fluid interfaces. Applications: Microalgae protein performance in emulsions and foams. Discussion on effects of pH, ionic strength, and extract purification. Interfacial, economic, and sustainability aspects compared to established proteins. Overview on current challenges and future prospects.